Neuroinflammation in glaucoma: A new opportunity. (April 2017) - ,; Bosco, Alejandra; Danias, John; Simon, John; Di Polo, Adriana; Kuehn, Markus H.; Przedborski, Serge; Raff, Martin; Trounce, Ian; Williams, Pete A.; Marsh-Armstrong, Nick; Howell, Gareth R.
Abstract: Mounting evidence suggests neuroinflammation is a key process in glaucoma, yet the precise roles are not known. Understanding these complex processes, which may also be a key in other common neurodegenerations such as Alzheimer's disease, will lead to targeted therapeutics for a disease that affects as many as 80 million people worldwide. Here, we define neuroinflammation as any immune-relevant response by a variety of cell types including astrocytes, microglia, and peripherally derived cells occurring in the optic nerve head and/or retina. In this review article, we first discuss clinical evidence for neuroinflammation in glaucoma and define neuroinflammation in glaucoma. We then review the inflammatory pathways that have been associated with glaucoma. Finally, we set out key research directions that we believe will greatly advance our understanding of the role of neuroinflammation in glaucoma. This review arose from a discussion of neuroinflammation in glaucoma at the 2015 meeting of The Lasker/IRRF Initiative for Innovation in Vision Science. This manuscript sets out to summarize one of these sessions; "Inflammation and Glaucomatous Neurodegeneration", as well as to review the current state of the literature surrounding neuroinflammation in glaucoma. Highlights: We describe the clinical relevance of inflammation in glaucoma. We define the sites of neuroinflammation in glaucoma. We discuss the roles of different cells and pathways in glaucoma. We discuss suggested 5 year goals as set about by the participants of the 2015 Lasker/IRRF Initiative session "Inflammation and Glaucomatous Neurodegeneration".